Unbiased Large Spectroscopic Surveys of Galaxies Selected by SPICA Using Dust Bands. (20th November 2017) - Kaneda, H.; Ishihara, D.; Oyabu, S.; Yamagishi, M.; Wada, T.; Armus, L.; Baes, M.; Charmandaris, V.; Czerny, B.; Efstathiou, A.; Fernández-Ontiveros, J. A.; Ferrara, A.; et al.
Abstract: The mid-infrared range contains many spectral features associated with large molecules and dust grains such as polycyclic aromatic hydrocarbons and silicates. These are usually very strong compared to fine-structure gas lines, and thus valuable in studying the spectral properties of faint distant galaxies. In this paper, we evaluate the capability of low-resolution mid-infrared spectroscopic surveys of galaxies that could be performed by SPICA . The surveys are designed to address the question how star formation and black hole accretion activities evolved over cosmic time through spectral diagnostics of the physical conditions of the interstellar/circumnuclear media in galaxies. On the basis of results obtained with Herschel far-infrared photometric surveys of distant galaxies and Spitzer and AKARI near- to mid-infrared spectroscopic observations of nearby galaxies, we estimate the numbers of the galaxies at redshift z > 0.5, which are expected to be detected in the polycyclic aromatic hydrocarbon features or dust continuum by a wide (10 deg 2 ) or deep (1 deg 2 ) blind survey, both for a given observation time of 600 h. As by-products of the wide blind survey, we also expect to detect debris disks, through the mid-infrared excess above the photospheric emission of nearby main-sequence stars, and we estimate their number. We demonstrate that the SPICA mid-infrared surveys will efficiently provide us with unprecedentedly large spectral samples, which can be studied further in the far-infrared with SPICA .